Correction of secondary deformity after Nuss procedure for pectus excavatum by means of cultured autologous cartilage cell injection. (2015) - Tamai, Motoki; Nagasao, Tomohisa; Yanaga, Hiroko; Hamamoto, Yusuke; Kogure, Tetsukuni; Tanaka, Yoshio
Highlights: Different strategies are available for the re-correction after pectus excavatum surgery. We cultured and propagated chondrocytes taken from a patient's auricular cartilage. The cultured chondrocytes are transplanted to the concave part of the chest. The chest shape improved and the transplanted cells consolidated, forming part of the chest wall. Transplantation of cultured chondrocytes is a useful treatment for pectus excavatum. Abstract: Introduction: For some cases of pectus excavatum, ideal chest shape cannot be achieved solely by performing the Nuss procedure. This manuscript presents a case where the residual deformity following Nuss was corrected using injection-transplantation of cultured autologous chondrocytes. Presentation of case: The treatment was performed for an 18-year-old male, who sought improvement of his chest shape after previously undergoing the Nuss procedure. A 1 cm 2 auricular cartilage piece was harvested from his ear. Chondrocytes were isolated from the cartilage piece and were cultured. The cultured chondrocytes were processed into gel form and were injection-transplanted to the deformed region of the patient's chest. The grafted chondrocytes consolidated in one month, presenting elasticity equivalent to ordinary costal cartilage. The patient's chest remains in an optimal shape after a one-year postoperative follow up. Discussion: Secondary correction of the chest deformity after previous operation for pectus excavatum is often tricky, because of the possible adhesion of the lungs or pericardium with the thoracic wall. Transplantation of cultured autologous chondrocytes does not require intra-thoracic maneuvers, and so is less invasive than other surgical interventions. Hence, priority can be placed, in some cases, on the chondrocyte transplantation rather than the re-correction of the thorax with the Nuss procedure or Ravitch procedure. Conclusion: Transplantation of cultured autologous chondrocytes is recommended as a useful option for secondary correction of chest deformity after the Nuss procedure.